PENGARUH PERLAKUAN FORMALIN TERHADAP KARAKTERISTIK KIMIA DAN SENSORIS IKAN SELAR KUNING (Caranx leptolepis) SEGAR - Dheka Adi Saputra; Merynda Indriyani Syafutri; Siti Hanggita (Universitas Sriwijaya, 2014)
The purpose of this research was to know the effect of formaldehyde treatments on chemical and sensory characterstics of fresh yellow stripe scad fish. This research used Factorial Completely Randomized design with two treatment factors and repliecated tree times. The treatment consist of the different formaldehyde concentration (0%, 25% and 50%), and self time (1, 3 and 6 days). The parameters observed were chemical characterstics (content of water, concent of protein, concent of formaldehyde), microbiology analysis (total plate count testing) and organoleptic characterstics (sensoris testing, score test method). The result of the research showed that the interaction of increasing of formaldehyde concentration and self time had significant effect on the water and formaldehyde content of yellow stripe scad fish. The factor increasing of formaldehyde concentration had significant effect on the protein content. The result of microbiology test (total plate count) showed that total of bacteria yellow stripe scad fish in formaldehyde treatment 0% was higher than increasing of formaldehyde concentration 25% and 50%. The organoleptic test showed that formaldehyde treatment 0% was stated fresh at first day, decline of quality at the third day and getting stinky at the sixth day. Yellow stripe scad fish with the treatment of concentration formaldehyde 25% stated decline of quality at the sixth day, whereas yellow stripe scad fish with formaldehyde treatment 50% still stated in fresh condition at the sixth day